Note-taking in consecutive interpreting: a review with special focus on Chinese-English literature - Sijia Chen (JoSTrans: The Journal of Specialised Translation)
Publications on note-taking in consecutive interpreting are reviewed, with special attention being awarded to literature written in Chinese and English. The review identifies two main streams of note-taking literature, a prescriptive stream and a descriptive stream. Prescriptive publications are concerned with the question "How should notes be taken?" They introduce the established note-taking systems and principles, and discuss how to teach them to students. The second stream, consisted of descriptive studies, tackles the question "How are notes taken?" The studies strive to approach the topic with scientific rigor by collecting data from simulated interpreting practices. Fruitful results have been created, but there are several limitations. The prescriptive stream lacks systematic empirical research to support the proposals. The descriptive stream is mostly product-oriented, lacking process research, and no study has designed true experiments to explain the causal relationships behind the observed phenomena. Cognitive load offers a promising perspective to approach the process of note-taking while contributing ample empirical data. It is therefore worthwhile to investigate cognitive load during note-taking in consecutive interpreting.